Long-term follow-up after percutaneous pulmonary valve implantation: sustained clinical benefit with evidence of persistent biventricular reverse remodeling and improved global performance. (25th November 2020) - Fusco, F; Uebing, A; Scognamiglio, G; Guarguagli, S; Kempny, A; Diller, G.P; Gatzoulis, M.A; Babu-Narayan, S.V; Li, W
Abstract: Background: Patients with native or post-surgical right ventricular outflow tract (RVOT) dysfunction often require several re-interventions. Percutaneous pulmonary valve implantation (PPVI) has recently been proposed as an attractive alternative to surgery, but there is still lack of data on long-term results. Aim: To determine the long-term outcome after PPVI and to investigate whether clinical benefit and cardiac performance improvement is achieved after the procedure. Methods and results: Seventy-eight patients (mean age 31.75±11.7) undergoing PPVI between April 2007 and July 2017 at Royal Brompton Hospital were retrospectively included in the study. The median follow-up was 6.1 years (2.1–11.2). Overall survival was 90.8%±4.1 at 6 years and 85%±5.9 at 11 years with freedom from valve failure (defined as either severe stenosis or regurgitation) of 87.6%±5 at 6 years of follow-up. Annual reintervention rate was 3.2% (95% CI 1.6–5.5). Infective endocarditis was a major concern with annual incidence rate of 1.6% (95% CI 0.5–3.4) and 50% of adverse outcome. Male sex (HR 3.2, 95% CI 1.3–7.9, p=0.013), age at procedure>50 years (HR 4.7, 95% CI 1.5–15.1, p=0.01) and residual mean gradient>25 mmHg at immediate postprocedural echo (HR 4.6, 95% CI 1.6–13.5%, p=0.006) were independently associated to the composite endpoint (including death, re-intervention, valve failure and arrhythmia). At latest follow-up, significant NYHA class (Pre Vs 6.1yrs Post p<0.0001) and cardiopulmonary test results improvement (peakVO2 p=0.01) and arrhythmic burden reduction (p=0.002) were found. Both cardiovascular magnetic resonance (CMR) and serial echocardiograms showed biventricular reverse remodeling (Pre Vs 1.3yrs Post CMR: RVEDVi p=0.0002, RVESVi p=0.0012, LVEDVi p=0.028). Furthermore, speckle tracking assessments demonstrated significant improvement of RV free wall GLS (Pre Vs 6.4yrs Post p=0.03) and LV GLS (p=0.01) at long-term. Moreover, concomitant improvement of RV relaxation properties was suggested by echo evidence of right atrial (RA) reverse remodeling (Pre Vs 6.4yrs Post RA area p=0.0001), increased RA strain (p=0.0005) and reduction of the patients with restrictive RV physiology (p<0.0001). Conclusion: PPVI is a reliable alternative to surgery with long-lasting favourable clinical effects associated with significant and persistent structural biventricular reverse remodeling and global systolic and diastolic functional improvement. Valve failure and infective endocarditis remain major complications during follow-up. Older and male patients and those with residual transvalvular gradients immediately post procedure are at higher risk of adverse clinical events, thus suggesting that re-intervention should be anticipated and that complete relief of RVOT obstruction should be pursued. Funding Acknowledgement: Type of funding source: None